2011
DOI: 10.1515/jpem.2011.300
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for adjunctive vitamin D therapy in the management of weight gain and metabolic side effects of second-generation antipsychotics

Abstract: , "A potential role for adjunctive vitamin D therapy in the management of weight gain and metabolic side effects of second-generation antipsychotics" (2011 AbstractSecond-generation antipsychotic (SGA) medications introduced about 20 years ago are increasingly used to treat psychiatric illnesses in children and adolescents. There has been a fi ve-fold increase in the use of these medications in U.S. children and adolescents in the past decade. However, there has also been a parallel rise in the incidence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…The results of our sensitivity analysis for different cutoffs on high vs low Vitamin D level (median split, 20 ng/mL or 30 ng/mL) suggest that the strength of the relationship between DEXA fat and liver fat increases as the vitamin D levels decrease. These results warrant further research but they do support the strategy proposed by others (20,41) to supplement vitamin D-deficient patients receiving antipsychotic drug therapy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results of our sensitivity analysis for different cutoffs on high vs low Vitamin D level (median split, 20 ng/mL or 30 ng/mL) suggest that the strength of the relationship between DEXA fat and liver fat increases as the vitamin D levels decrease. These results warrant further research but they do support the strategy proposed by others (20,41) to supplement vitamin D-deficient patients receiving antipsychotic drug therapy.…”
Section: Discussionsupporting
confidence: 75%
“…Further, the evidence supporting treatment of low vitamin D level has been equivocal. In a small 8 week pilot and feasibility study in inpatient adolescents (n ϭ 12), 2000 IU Vitamin D daily was associated with an increase in serum vitamin D concentration, but was not associated with consistent changes in body weight (41). Similarly, a small, 8 week pilot study evaluating the effect of daily supplementation at 2000 IU in 19 schizophrenic adults treated with antipsychotics with low vitamin D levels showed a significant improvement in vitamin D level from baseline, but no change in anthropomorphic or fasting metabolic parameters (42).…”
Section: Discussionmentioning
confidence: 93%
“…A recent trial found that melatonin was helpful in decreasing weight gain in bipolar patients with antipsychotic-induced weight gain 80. Vitamin D381 and omega 3 fatty acids have been proposed as possible therapies in the case of antipsychotic induced weight gain as well.…”
Section: Metabolic Syndrome and Long-term Risk Factorsmentioning
confidence: 99%
“…Although the relationship is unclear, it has been hypothesized that obesity could be a cause or a result of inadequate vitamin D and calcium status [33]. Smoking has also been associated with vitamin D inadequacy; among women in a Swiss population, current smokers consumed significantly less vitamin D and calcium than women who never smoked [34].…”
Section: Discussionmentioning
confidence: 99%